Kebebasan Manusia: Telaah terhadap Corak Teologi dalam Tafsir Departemen Agama - Masri Mansoer (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2006)
In 1967, the Government of the Republic of Indonesia formed the Quran Translation Committee, and this activity was completed in 1975 with the production of the Quran and Its Translation. Then, in 1972, the Council for the Organization of Quranic Exegesis was established and completed its Quran and Exegesis in 1984, consisting of 1 (one) volume of the Introduction to the Quran and its Exegesis and 10 (ten) volumes of the Quran and its Exegesis. This is one of the exegesis books collectively written in the modern era of the Islamic world. Considering the reasons for the emergence of this exegesis, both internal and external factors of Islamic thought surrounding the reference exegeses, raises the question of how the Department of Religion’s Quran and its exegesis interpret verses about human freedom. This paper will focus on human freedom related to Free Will and Predestination, and its connection to the concept of faith.